Strategies for targeting the P2Y12 receptor in the central nervous system. (1st September 2022) - Ma, Ben B.; Montgomery, Andrew P.; Chen, Biling; Kassiou, Michael; Danon, Jonathan J.
Graphical abstract: Abstract: The purinergic 2Y type 12 receptor (P2Y12 R) is a well-known biological target for anti-thrombotic drugs due to its role in platelet aggregation and blood clotting. While the importance of the P2Y12 R in the periphery has been known for decades, much less is known about its expression and roles in the central nervous system (CNS), where it is expressed exclusively on microglia – the first responders to brain insults and neurodegeneration. Several seminal studies have shown that P2Y12 is a robust, translatable biomarker for anti-inflammatory and neuroprotective microglial phenotypes in models of degenerative diseases such as multiple sclerosis and Alzheimer's disease. An enduring problem for studying this receptor in vivo, however, is the lack of selective, high-affinity small molecule ligands that can bypass the blood–brain barrier and accumulate in the CNS. In this Digest, we discuss previous attempts by researchers to target the P2Y12 R in the CNS and opine on strategies that may be employed to design and assess the suitability of novel P2Y12 ligands for this purpose going forward.